2022
DOI: 10.1590/0001-3765202220211287
|View full text |Cite
|
Sign up to set email alerts
|

Toxicological assessment of SGLT2 inhibitors metabolites using in silico approach

Abstract: Sodium-glucose cotransporter 2 inhibitors (SGLT2i) are the latest class of drugs approved to treat type 2 DM (T2DM). Although adverse effects are often caused by a metabolite rather than the drug itself, only the safety assessment of disproportionate drug metabolites is usually performed, which is of particular concern for drugs of chronic use, such as SGLT2i. Bearing this in mind, in silico tools are efficient strategies to reveal the risk assessment of metabolites, being endorsed by many regulatory agencies.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 47 publications
(35 reference statements)
0
2
0
Order By: Relevance
“…However, their amounts were almost too low to quantify them using the above method [ 29 ]. In the study of De Jesus et al [ 40 ], the above-mentioned structures for the mentioned CANA metabolites were confirmed.…”
Section: Gliflozins (Sglt2 Inhibitors)mentioning
confidence: 76%
See 3 more Smart Citations
“…However, their amounts were almost too low to quantify them using the above method [ 29 ]. In the study of De Jesus et al [ 40 ], the above-mentioned structures for the mentioned CANA metabolites were confirmed.…”
Section: Gliflozins (Sglt2 Inhibitors)mentioning
confidence: 76%
“…These SGLT2 inhibitors that metabolize through glucuronidation can be subsequently eliminated with urine. Such an excretion process can be facilitated by organic anion transporters, which are responsible for the uptake of various organic anionic compounds such as glucuronidation and sulfation drug metabolites [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations